The Motives of the Feminist #MeToo Movement in Václav Havel's Plays. (3rd July 2022) - Čulík, Jan
ABSTRACT: Václav Havel (1936–2011) was for many people in the Czech Republic the most significant and certainly the most revered cultural and political figure of the past half a century. In the 1960s, Havel became the most important representative of East European absurd drama. His work was banned after the 1968 Warsaw Pact invasion of Czechoslovakia. Gradually, throughout the 1970s and 1980s, Havel emerged as one of the most important Czechoslovak dissidents and after the fall of communism in 1989, he was elected President of Czechoslovakia and then of the Czech Republic. In all, Havel wrote 13 plays. In them, he criticizes the shameless and arrogant quest for power, which is usually conducted by the abuse of language. This article, however, is the first in the history of criticism of Havel's plays which points out that from as early as the 1960s, Havel systematically included scenes of sexual manipulation of young women by ageing men, in his plays, thus anticipating the #MeToo movement by many decades.